The foundations of early modern Europe, 1460-1559 - Rice, Eugene F., author; Grafton, Anthony, author (New York W.W. Norton, 1970)
This synthesis of Europe's Renaissance and Reformation periods thematically traces the transition from the medieval to the modern. The major themes of the book include technological breakthroughs and their social and economic consequences, the connections between the discovery of new lands and the recovery of ancient learning, Europe's economic expansion, humanist culture, the formation of the early modern state, and reform and revolution in the Church
Donated by Prof. M. Riley 1.19.16
Keywords: Renaissance; Reformation; Europe -- Civilization